Incidence and characteristics of antituberculosis drug-induced hepatotoxicity in children: a preliminary study - Bina Akura; Hanifah Oswari; Bambang Supriyatno; Najib Advani (Paediatrica Indonesiana, 2009)
Background Antituberculosis drugs show good efficacy but have adverse effects including hepatotoxicity.